Flattening the curve: how Eliud Kipchoge`s unique physiology attenuates his agerelated performance decline - Paris, H. L.; Wiggins, C. C.; Shei, R.-J. (European Journal of Sport Science, 2020)
The aim of this study was to examine the physiological profile of Eliud Kipchoge in his attempt at a master`s M50 (age 50-54) marathon World Record. Additionally, by comparing Kipchoge`s physiology over the past two decades with those of healthy individuals, we document his age-related decline in performance, thereby demonstrating the extreme limit of what is understood to be physiologically plausible. Coupled with his eclipsing of the World Record, Kipchoge`s data demonstrate that although aging remains inevitable, technological advancements and world class physiology slow age-related decrements in health and performance.